Unlocking the potential of relational pedagogy : reimagining teaching, learning and policy for contemporary schooling - Riddle, Stewart; Hickey, Andrew T., 1977- (Abingdon, Oxon ; New York, NY : Routledge, 2025)
"This book is a useful guide for educators who seek to better engage students in rich, meaningful learning, outlining a clear set of key concepts and principles for relational pedagogy in school classrooms. Emphasising the complex interpersonal encounters that mediate the social, cultural and political dynamics of the school as a shared space, the authors draw attention to the myriad relationships that constitute the social context of the school and the effects these have on teaching, learning and engagement. The relationships between students and teachers directly affect the experience of education, how learning unfolds and overall educational outcomes. Building on scholarly work and school practices, this book argues that relational pedagogy should be at the centre of teaching and learning in schools, in order to drive positive educational change. It further demonstrates the potential of relational pedagogy in the classroom through vignettes and examples from practice to highlight how these concepts can be applied in teaching and school leadership. Presenting a compelling new framework for relational pedagogy, this book will be of interest to teacher educators, postgraduate students of education, policy and school leaders"--
Preface -- Introducing relational pedagogy -- Keywords for relational pedagogy -- Education policy making and relationality -- Towards authentic relationality -- Bringing the educational relation to life -- Propositions towards a more relational schooling -- Afterword : on the (im)possibilities of relational pedagogy.
Keywords: Interaction analysis in education; Teacher-student relationships; School environment; EDUCATION / General; EDUCATION / Classroom Management; EDUCATION / Educational Policy & Reform / General